Year of the rocket [Chinese space research]. - Oberg, J. (IEEE spectrum)
The Chinese have the space capabilities of the most advanced industrialized countries. They build and launch long-range missiles, put satellites in orbit, and, as of late 2000, plan a national strategy for manned space flight. But detractors, suspicious of China's rapid progress, allege it leap-frogged years of R&D by spying on the West. The author examines whether there is anything to these charges, or whether China has achieved success on its own. The truth, it seems, is more complex than either extreme